(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
On the basis of some significant inconsistencies in the critical bibliography of Eneide travestita, where the appearance of the poem is traced back sometime to 1632, sometime to ’33, other times to ’34, this essay describes and reorders the materials available at the present moment on Lalli’s rendition, on the history of its creation, and on the interactions between the author and the Roman court. Once established the strong affinity that ties the two “Facciotti” printing, I suggest as hypotetical publishing date the period between the end of 1633 and the first months of 1634; therefore I reconstruct the close relationship between the author, the cardinal Bernardino Spada, and Nicola Villani. Lastly, I highlight the foremost points of contact with Bracciolini’s mock-heroic tradition.